IMPLEMENTASI PROJEK KEWIRAUSAHAAN DALAM MENDUKUNG PROFIL PELAJAR PANCASILA DI SMAN 1 SIKUR - Hardiansyah, Hardiansyah (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2023)
Abstract: Pancasila Student Profile Entrepreneurship is able to realize idealistic dreams and develop their own potential with the emergence of 6 elements of the Pancasila Student Profile in Entrepreneurship Activities. The data analysis technique used in this study is descriptive qualitative data analysis using a qualitative triangulation model. The results of this study are the development of entrepreneurial projects in supporting the profile of Pancasila students in the form of the Merdeka curriculum which is modified into 1 program, the Entrepreneurship Project program where the program is scheduled on Fridays and Saturdays and the person in charge appears on a schedule that implements the learning process of entrepreneurship projects so as to develop talent in students and enthusiasm in creating a product, such as Typical Sasak Food, Typical Sasak Snacks (cakes), Candied Papaya, Efficacious Drinks, and Crafts. In the Entrepreneurship Project that supports the profile of Pancasila student profiles, SMAN 1 Sikur applies the independent curriculum (School of Mobilization), as it can encourage an entrepreneurial spirit through the Project to Strengthen Pancasila Student Profiles (P5) with the theme of entrepreneurship. Where the teacher of SMAN 1 Sikur hopes that with this the teacher becomes a facilitator and students must play an active role in the process or carry out activities in learning. Keywords: Entrepreneurship Project, Profile of Pancasila Supporters. Abstrak: Profil Pelajar Pancasila Kewirausahaan mampu mewujudkan mimpi idealisme dan mengembangkan potensi diri sendiri dengan munculnya 6 Elemen Profil Pelajar Pancasila dalam berkegiatan Kewirausahaan. Tehnik analisis data yang digunakan dalam penelitian ini yaitu analisis data kualitatif deskriptif dengan model Triangulasi kualitatif. Hasil penelitian ini diperoleh informasi dan data tentang implementasi projek kewirausahaan dalam mendukung profil pelajar pancasila dituangkan ke dalam Kurikulum Merdeka yang di modifikasi menjadi 1 program, program projek kewirausahaan yang dimana program itu disusun terjadwal pada hari Jum’at dan hari Sabtu dan muncul penanggung jawab secara terjadual itulah yang mengimplementasikan pada proses pembelajaran projek kewirausahaan sehingga mengembangkan bakat pada siswa dan semangat dalam menciptakan sebuah prodak, seperti Makanan Khas Sasak, Jajanan (kue) Khas Sasak, Manisan Pepaya, Minuman yang Berkhasiat dan Kerajiaan Tangan. Dalam Projek kewirausahaan yang mendukung profil pelajar pancasila SMAN 1 Sikur mengaplikasikan kurikulum merdeka (Sekolah Penggerak), sebagai dapat mendorong jiwa kewirausahaan melalui Projek Penguatan Profil Pelajar Pancasila (P5) tema kewirausahaan. Dimana guru SMAN 1 Sikur berharap dengan adanya hal tersebut guru menjadi fasilitator dan siswa yang harus berperan aktif dalam proses atau berkegiatan dalam pembelajaraan. Kata Kunci: Projek Kewirausahaan, Profil Pendukung Pancasila.